Penerapan Metode Median Filtering untuk Optimasi Deteksi Wajah pada Foto Digital - Sunardi Sunardi; Anton Yudhana; Setiawan Ardi Wijaya (Politeknik Negeri Cilacap, 2022)
Face detection in digital photos aims to get the face area in the photo. Problems often occur when detecting faces, namely there is a lot of noise in digital photos so that it affects the detection process. Therefore, in this study apply the median filtering method to improve digital photos by reducing noise in the photos to be tested. The advantage of using this filter is to keep the edges smooth while reducing noise which aims to improve image quality. The ability of this method is measured using the parameters of Mean Square Error (MSE) and Peak Noise to Signal Ratio (PNSR). When the MSE value obtained is low and the PNSR value obtained is high, the results can be said to be good. The method used to detect faces in this research, viola-jones, was chosen because it is one of the face detection procedures with a high level of accuracy and good computational ability. The sample used in this study consisted of 10 digital photos taken using a Samsung A11 smartphone camera with a resolution of 13 mega pixels and 8 mega pixels in JPEG format. The results obtained in this study are the best error values in MSE 0.9517 and PSNR 24.2804. Based on these results, it can be concluded that the mean filtering method is feasible to be used in the case of face detection in this digital photo.